1993
DOI: 10.1016/0169-5983(93)90035-9
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a shock wave with a high-speed vortex ring

Abstract: This is a detailed experimental study of the behavior of diffraction and refraction of a shock front resulting from the interaction of a shock wave and a vortex ring. A spherical shock wave impinges on a vortex ring which is traveling at a high speed in the opposite direction. The configuration of the wave front is visualized by a shadowgraph technique using a pulse dye laser. The shock front is influenced by the non-uniform flow induced by the vortex and diffracted around the vortex core. The shock front pass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 8 publications
(8 reference statements)
3
22
0
Order By: Relevance
“…As shown in previous studies [19,28], the shock wave interaction process is divided into two sections: the outer and the central parts of the vortex ring. In shock wave interactions with square vortex loops, the behaviour generating the retarded/diffracted shock waves at the outer and central parts of the vortex loop resembles that of interaction with a circular vortex loop.…”
Section: The Images [(B) (H)] [(C) (I)] and [(D) (J)]mentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in previous studies [19,28], the shock wave interaction process is divided into two sections: the outer and the central parts of the vortex ring. In shock wave interactions with square vortex loops, the behaviour generating the retarded/diffracted shock waves at the outer and central parts of the vortex loop resembles that of interaction with a circular vortex loop.…”
Section: The Images [(B) (H)] [(C) (I)] and [(D) (J)]mentioning
confidence: 99%
“…Since the early 1990s, there have been experimental, numerical, and theoretical investigations of shock wave interaction with vortex rings [20-22, 26, 27]. Minota [28] experimentally investigated shock-vortex ring interactions when the shock wave impinges head-on. She showed that the diffracted shock wave which interacts with the vortex ring propagates towards the centre of the vortex ring, which results in the shock wave focusing at the centre of the vortex ring.…”
Section: Introductionmentioning
confidence: 99%
“…Animals are wise enoug to take advantage of the reaction forces variously. A vortex ring generated by a shock impulse [7]. Figure 3.…”
Section: Mechanical Aspectmentioning
confidence: 99%
“…5 No matter the initial conditions in which a vortex loop is generated, there are three stages in the propagation of a vortex loop: formation, development, and decay. Although numerous authors have reported both experimental and numerical studies on vortex loop characteristics covering the incompressible, 6-12 compressible, 13,14 and detonation regimes, 15 there is a scarcity of data on compressible vortex loops and jets generated from nozzles with singular corners. Compressibility alone has a great influence in the propagation of vortex loops.…”
Section: Introductionmentioning
confidence: 99%